Eating Behavior in Response to Psychological Distress Emerging Adulthood Women - Rahmawati, Vivin Eka; Azizah, Ninik; Wulandari, Dewi Triloka; Fatimah, Nurul (International Journal Of Health Science, 2026)
Emerging adulthood is a crucial transitional period prone to psychological distress, during which women are twice as likely to experience emotional mental health disorders that may trigger eating disorders. This study aims to examine the relationship between depression, anxiety, and stress and eight dimensions of eating behavior in young adult women. The study employed a quantitative correlational design with a cross-sectional approach, involving a sample of 127 female respondents (aged 17–25 years; 79.5% rural, 20.5% urban) from Blaru Village (Pati Regency) and Rejoso Village (Jombang Regency). The Depression Anxiety Stress Scales-21 (DASS-21) was used to measure psychological distress, while eating behavior characteristics were assessed using the Adult Eating Behavior Questionnaire (AEBQ). The results of the descriptive analysis showed a very high level of emotional distress among the respondents, with a prevalence of moderate to very severe depression reaching 100%, severe to very severe anxiety at 96.1%, and severe to very severe stress at 73.2%. The Spearman rank correlation test revealed a specific dualism in eating responses, in which depression, anxiety, and stress were found to have highly significant positive correlations (ρ < 0.01). The anxiety variable showed the strongest correlation with the tendency to refuse food or undereat due to emotions (rs = 0.359; ρ = 0.000). Conversely, psychological distress did not show a significant relationship (ρ > 0.05) with the six subscales of biological homeostasis-based eating behaviors (such as Hunger and Satiety Responsiveness). This study concludes that emotional mental disorders do not impair the basic mechanical functions of the digestive system but rather selectively disrupt the regulation of emotional eating control at the higher cortical cognitive level (cognitive override).